Russia and Europe Under Sanctions: Problems of Energy Development - Zaynutdinov, Ruslan Raisovich (International Journal of Energy Economics and Policy, 2015)
Reciprocal application of sanctions due to geopolitical instability in Ukraine, led to the rupture of economic ties and investment cooperation between the Russian Federation and the European Union. Further escalation of the confl ict can lead to the formation of a new cold war and the reorientation of the world economy. In connection with this assessment of the risks and challenges of mutual economic development in the Eurasian continent becomes particularly relevant theme. The study reviews the current economic partnership between the Russian Federation and the European Union. Actualized data on the implementation of joint investment projects. In conclusion reveals the degree of mutual economic risks in case of continuing the policy of restrictive measures. Keywords: Sanctions, Restrictive Measures, Energy Dependence, The Reorientation of Markets JEL Classifications: F63; O52; P17; P27